(untitled) (International Journal of Physiotherapy, 2025)
Background: Breast cancer is a significant cause of cancer-related morbidity and mortality worldwide, including in Malaysia. Post-mastectomy complications, such as lymphedema and upper limb disability, significantly affect health-related quality of life. Physiotherapy-led rehabilitation plays a critical role, yet little research has explored physiotherapists’ awareness of these issues in Malaysia. This study aimed to identify the knowledge and awareness regarding post-mastectomy lymphedema management and upper limb disability among Malaysian physiotherapists. Methods: A cross-sectional study was conducted with 111 physiotherapists through an online survey. Participants completed a validated self-structured questionnaire encompassing eight sections: demographics, clinical practice, knowledge, management of lymphedema and disability, awareness of physiotherapists’ roles, awareness levels, and learning needs. Data analysis assessed awareness and influencing factors. Results: Physiotherapists displayed commendable awareness, with an overall average accuracy of 72.88%. Participants with Bachelor’s degrees achieved higher accuracy compared to diploma holders, underlining the importance of educational background and clinical experience in shaping awareness (p<0.05). Conclusion: The findings highlight the need for personalized education and ongoing professional development to enhance physiotherapists’ competence in managing post-mastectomy complications. This underscores their pivotal role in improving patient recovery and quality of life.